Race and Shame in Toni Morrison’s Sula: A Thematic Review - HASSAN, AHMED FlAYIH; BHAVANI, E. (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
In this review, Toni Morrison’s Sula is discussed in terms of how she explores the intertwined themes of race and shame as powerful forces of Black female identity and communal life. The novel is set in the fictional Black neighbourhood of the Bottom and gives the lives of its characters who are not only marginalized by race. Morrison lays bare how shame acts as a tool of social control sustained by the community’s moral code as transmitted through the character of Sula Peace, whose refusal to conform points to the suppression of the social ills that once troubled the community. It examines how shame gets manufactured and handed down through at least two generations in the mother-daughter dynamic and around shared perceptions of the Black female body. In the end then, Morrison employs the politics of shame to undermine rigid social norms so that to do away with them, it is possible for Black women to imagine other possibilities of selfhood and agency that transcend race and conformity.